2009
DOI: 10.1093/hmg/ddp431
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of PPAR /  stimulates utrophin A expression in skeletal muscle fibers and restores sarcolemmal integrity in mature mdx mice

Abstract: A therapeutic strategy to treat Duchenne muscular dystrophy (DMD) involves identifying compounds that can elevate utrophin A expression in muscle fibers of affected patients. The dystrophin homologue utrophin A can functionally substitute for dystrophin when its levels are enhanced in the mdx mouse model of DMD. Utrophin A expression in skeletal muscle is regulated by mechanisms that promote the slow myofiber program. Since activation of peroxisome proliferator-activated receptor (PPAR) beta/delta promotes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 56 publications
4
117
0
1
Order By: Relevance
“…Pharmacological activation of the muscle-specific PPAR␤/␦ isoform promotes muscle development, myonuclear accretion, and satellite cell proliferation and restores sarcolemmal integrity in dystrophic mice models (17,19,23,50,51), strongly supporting a role for PPAR␤/␦ in regulating postnatal muscle growth and development. However, no study has yet clearly revealed the molecular mechanism(s) through which PPAR␤/␦ regulates skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Pharmacological activation of the muscle-specific PPAR␤/␦ isoform promotes muscle development, myonuclear accretion, and satellite cell proliferation and restores sarcolemmal integrity in dystrophic mice models (17,19,23,50,51), strongly supporting a role for PPAR␤/␦ in regulating postnatal muscle growth and development. However, no study has yet clearly revealed the molecular mechanism(s) through which PPAR␤/␦ regulates skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 93%
“…Microarray and subsequent expression analysis collectively confirm that PPAR␤/␦ positively regulates Gasp-1 gene expression; as such, we suggest that Gasp-1 represents a novel muscle-specific downstream target of PPAR␤/␦. Previously published work has revealed that PPAR␤/␦ expression is greater in atrophying muscle tissue isolated from mdx mice, a mouse model of Duchenne muscular dystrophy (23). Based on this observation, we next wanted to ascertain whether increased endogenous PPAR␤/␦ expression, as seen in mdx mice, would induce Gasp-1 expression in vivo.…”
Section: Primary Myoblasts Derived From Ppar␤/␦-null Mice Have Reducementioning
confidence: 97%
See 1 more Smart Citation
“…The ability of PDN to upregulate utrophin is well known; the underlying mechanism involves both enhanced NF-AT transcription and translation. 27,84 Utrophin might act as a surrogate for dystrophin and associate with b-DG to rescue the complex. 84 A critical tyrosine residue of b-DG is exposed in the absence of dystrophin, and the consequent phosphorylation contributes to internalization and ubiquitin -related degradation of b-DG.…”
Section: Discussionmentioning
confidence: 99%
“…27,84 Utrophin might act as a surrogate for dystrophin and associate with b-DG to rescue the complex. 84 A critical tyrosine residue of b-DG is exposed in the absence of dystrophin, and the consequent phosphorylation contributes to internalization and ubiquitin -related degradation of b-DG. Nonetheless, bortezomib, a proteasome inhibitor, has been found to increase the expression of dystrophin-glycoprotein complex in muscles of mdx mice and in DMD biopsies.…”
Section: Discussionmentioning
confidence: 99%